Milk yield and lactation stage are associated with positive results 5 to ELISA for Mycobacterium avium subsp. paratuberculosis 6 in dairy cows from Northern Antioquia, Colombia: 7 a preliminary study (2016)
ABSTRACT: Paratuberculosis is a slow-developing infectious disease characterized by chronic granulomatous enterocolitis. This disease has a variable incubation period from 6 months to over 15 years and is caused by Mycobacterium avium subsp. paratuberculosis (MAP). Some studies have been conducted in cattle during the last decades in Colombia. However, those studies were designed using relatively small populations and were not aimed to establish prevalence. This study aimed to determine the MAP seroprevalence in selected dairy herds and to explore risk factors associated with the serology results. Serum samples and related data were collected from 696 randomly selected bovines in 28 dairy herds located in 12 different districts in one of the main dairy municipalities in Colombia (San Pedro de los Milagros). The samples were analyzed using a commercial ELISA kit. The information on risk factors was analyzed using a logistic regression. The apparent seroprevalence was 3.6 % (1/28) at the herd level and 2 % (14/696) at the animal level. The number of days in milk production between 100 and 200 days and over 200 days and the daily milk production between 20 and 40 L/cow and over 40 L/cow were associated with MAP seropositivity with odds ratios of 4.42, 3.45, 2.53, and 20.38, respectively. This study demonstrates the MAP seroprevalence in dairy herds from Antioquia and the possible relationship between MAP seropositivity, milk yield, and lactation stage.